A Method for the Simultaneous Cleansing of H2S and SO2. (17th January 2016) - Uzun, Dzhamal R.; Razkazova-Velkova, Elena; Beschkov, Venko; Petrov, Konstantin
Abstract : A method for the simultaneous electrochemical purification of hydrogen sulfide and sulfur dioxide from sea water or industrial wastes is proposed. Fundamentally the method is based on the electrochemical affinity of the pair H2 S and SO2 . The reactions (oxidation of H2 S and reduction of SO2 ) proceed on а proper catalyst in a flow reactor, without an external power by electrochemical means. The partial curves of oxidation of H2 S and reduction of SO2 have been studied electrochemically on different catalysts. Following the additive principle the rate of the process has been found by intersection of the curves. The overall process rate has been studied in a flow type reactor. Similar values of the process rate have been found and these prove the electrochemical mechanism of the reactions. As a result the electrochemical method at adequate conditions is developed. The process is able to completely convert the initial reagents (concentrationsC H 2 S, S O 2 = 0 ), which is difficult given the chemical kinetics.